2007
DOI: 10.1002/ajmg.a.32062
|View full text |Cite
|
Sign up to set email alerts
|

Major gene and multifactorial inheritance of mandibular prognathism

Abstract: Mandibular prognathism typically shows familial aggregation. Various genetic models have been described and it is assumed to be a multifactorial and polygenic trait, with a threshold for expression. Our goal was to examine specific genetic models of the familial transmission of this trait. The study sample comprised of 2,562 individuals from 55 families. Complete family histories for each proband were ascertained and the affection status of relatives were confirmed by lateral cephalograms, photographs, and den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
79
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 29 publications
6
79
3
Order By: Relevance
“…The etiology of class III malocclusion is a curious issue and there is much to be clarified and understood. To describe class III malocclusion, environmental and genetic factors are playing the major role and it follows the autosomal dominant mode of inheritance was confirmed from altered studies 1,7,8) . However, the relationship concerning cranialbase morphology related to genetic heritability and Class III malocclusion is not entirely understood.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The etiology of class III malocclusion is a curious issue and there is much to be clarified and understood. To describe class III malocclusion, environmental and genetic factors are playing the major role and it follows the autosomal dominant mode of inheritance was confirmed from altered studies 1,7,8) . However, the relationship concerning cranialbase morphology related to genetic heritability and Class III malocclusion is not entirely understood.…”
Section: Introductionmentioning
confidence: 94%
“…Such skeletal disparity is consequences from growth resentment between maxilla and mandible, therefore creating a concave facial profile. Class III craniofacial structure is a concern of the fact that many patients having this malocclusion are treated routinely with orthodontics 7) . The concern of development in class III subjects has become more important because of the increasing awareness in enhancing treatment timing and planning in dentofacial orthopedics.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analysis of families with the Class III phenotype supports the hypothesis of polygenic inheritance. [4][5][6][7] Recently, Cruz et al 8 in a study on 55 Brazilian families with mandibular prognathism concluded that there is a major gene that influences the expression of the trait with clear signs of Mendelian inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…17 These investigations suggested that MP has an autosomal dominant inheritance with or without incomplete penetrance. Interestingly, although Yamaguchi et al 5 reported that three markers (D1S234, D6S1689, and D19S566) were associated with MP in Koreans/ Japanese, a follow-up study of Cruz et al 18 showed that these markers did not have any evidence of linkage in the Brazilian population.…”
Section: Introductionmentioning
confidence: 99%
“…Cruz et al 17 also performed a segregation analysis on 55 Brazilian families with 2562 relatives. Their study was similar to this study in terms of the subject number and the recruited subtype of Class III malocclusion a q_A indicates the frequency of the allele A in the population when Hardy-Weinberg equilibrium is assumed; t, transmission parameter (the probability that a parent transmits allele A to offspring); s 3 2 , the variance of the polygenic effect incorporating three polygenic loci.…”
mentioning
confidence: 99%